STRATEGI PERAWATAN KOLEKSI NASKAH LONTAR BALI DI PERPUSTAKAAN BALAI BAHASA BALI - Anik Hartini Ari, Ni Wayan; Ginting, Richard Togarata; Premierita Haryanti, Ni Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2018)
ABSTRACT The purpose of this research is to apply strategy of lontar bali manuscript’s preservation in Perpustakaan Balai Bahasa Bali.This research uses descriptive qualitative research method. Data collection techniques are observation, interviewing, documentation,and literature studies.Informants from this research are the head of affairs and librarian,which amounted to three peoples.This research was conducted during February-April 2018.The results of this study indicate that the maintenance of lontar bali manuscripts in library, treats manuscript lontar bali by applying conventional treatment.The application of lontar bali manuscript’s preservation in library is very helpful in preserving the cultural heritage assets from damage condition.The damage that occurred in lontar bali were broken or torned and faded.The treatments of lontar bali manuscript’s preservation is done by giving lemongrass oil and pecan oil on manuscript.The obstacles faced in the treatment of lontar bali manuscript are lontar bali conditions by old manuscript and human resources competences to preserve lontar bali manuscript. Keywords: manuscript, lontar bali, preservation